GAMMA-RAY BURST REVERSE SHOCK EMISSION IN EARLY RADIO AFTERGLOWS - Resmi, Lekshmi; Zhang, Bing (The Astrophysical journal, 2016)
ABSTRACT Reverse shock (RS) emission from gamma-ray bursts is an important tool in investigating the nature of the ejecta from the central engine. If the magnetization of the ejecta is not high enough to suppress the RS, a strong RS emission component, usually peaking in the optical/IR band early on, would provide an important contribution to early afterglow light curve. In the radio band, synchrotron self-absorption may suppress early RS emission and also delay the RS peak time. In this paper, we calculate the self-absorbed RS emission in the radio band under different dynamical conditions. In particular, we stress that the RS radio emission is subject to self-absorption in both RSs and forward shocks (FSs). We calculate the ratio between the RS to FS flux at the RS peak time for different frequencies, which is a measure of the detectability of the RS emission component. We then constrain the range of physical parameters for a detectable RS, in particular the role of magnetization. We notice that unlike optical RS emission which is enhanced by moderate magnetization, moderately magnetized ejecta do not necessarily produce a brighter radio RS due to the self-absorption effect. For typical parameters, the RS emission component would not be detectable below 1 GHz unless the medium density is very low (e.g., n < 10−3 cm−3 for the interstellar medium and A* < 5 × 10−4 for wind). These predictions can be tested using the afterglow observations from current and upcoming radio facilities such as the Karl G. Jansky Very Large Array, the Low-Frequency Array, the Five Hundred Meter Aperture Spherical Telescope, and the Square Kilometer Array.